Analiza uspešnosti prodaje gozdnih lesnih sortimentov v gozdarski zadrugi lastnikov gozdov Pohorje - Kozjak - Černač, Gregor (Acta silvae et ligni, 2020)
We analyzed the sale of forest wood products in the Pohorje - Kozjak private forest owner cooperative (hereinafter the cooperative) for the period 2013%2017. Data on the quantity and prices of forest wood products, sellers and the market were obtained from financial records of sales. To analyze the effectiveness of forest wood products sales in the cooperative, we compared cooperative prices with average prices in Slovenia. In addition, we surveyed cooperative members to assess their satisfaction with purchase prices and the operation of the cooperative. The cooperative purchased most of the wood from nonmembers and largely sold it to neighboring Austria. The average purchase price for forest wood products was 18.3 % higher in the cooperative compared to the Slovenian average. On average, members of the cooperative are satisfied with cooperative prices, although 37.5 % of them also sold their forest wood products to other purchasers, which is a long-term problem. Based on the results, we conclude that the cooperative business model for private forest owners is effective and that the government should promote and financially support such business cooperation models through forest policy instruments.
Keywords: business cooperation; forest cooperative; gozdarske zadruge; lastništvo gozdov; poslovno povezovanje; private forests; timber market; trg lesa; zasebni gozdovi